E-Paper Analisa Daily Untuk Meningkatkan Keterampilan Berpikir Kritis Masyarakat Anti Hoax - Sisi Rosida; Eka Surya Fitriani; Nurbaiti Ali; Eka Perananta; Febriansyah Febriansyah (Journal on Education, 2024)
This research aims to determine the Daily Analysis E-Paper to improve the critical thinking skills of the anti-hoax community in Suka Damai Village. This research uses an explanatory method with a quantitative approach. The population in this study includes residents of Suka Damai Village. The sampling technique used in this research is Total Sampling. The total sample used in this research was 50 people. The data collection technique used was a questionnaire. The data analysis technique used is simple linear regression with the help of IBM SPSS V22 software. The results of this research show that the correlation test between the 2 variables for the level of Critical Thinking Skills of the Anti-Hoax community is known to have a value of 0.634, so it is included in the high category. Based on the results of the regression test, it is known that the influence value of the level of information literacy skills in efforts to prevent hoaxes in Suka Damai Village is Y = -0.219 + 0.304 by other factors not studied.